Fraud Prevention System with Whistleblowing System in Health Services: A Systematic Review - Ridwan, Ridwan; Munadi, Said; Fahlevi, Heru; Nadirsyah, Nadirsyah (BPJS Kesehatan, 2024)
The objective of this study is to ascertain the strategies employed in mitigating fraudulent activities within the realm of health services through the utilization of a whistleblowing mechanism. Methods: The present study employed a systematic review approach to examine relevant literature by utilizing specific keywords such as